SPORT MANAGEMENT: WHY THE FIGHT FOR POINTS ACCRUED IN BRAZILIAN FOOTBALL CHAMPIONSHIP? (Fiep Bulletin - online, 2011)
Seeking to show the reason and the fixedness of the Brazilian Championship by points accrued started in 2003 through a literature review and no-structure interviews guided type, quoted by Gay (1976), we chose according to their relevance within the field of soccer management, three social actors that allowed us to cross the information, identify the reasons for this choice of dispute. We conclude that the main reasons recorded were the pressure of the media at that time, claims for justice by sporting clubs and a new trend coming from European.
Keywords: Soccer; Sports Management; Brazilian Championship